Heart Team/Guidelines Discordance Is Associated With Increased Mortality: Data From a National Survey of Revascularization in Patients With Complex Coronary Artery Disease. (11th January 2021) - Witberg, Guy; Segev, Amit; Barac, Yaron D.; Raanani, Ehud; Assali, Abid; Finkelstein, Ariel; Roguin, Ariel; Sahar, Gideon; Vaknin-Assa, Hana; Bolotin, Gil; Eitan, Amnon; Klempfner, Robert; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Practice guidelines emphasize the role of the SYNTAX score (SS; Synergy Between PCI With TAXUS and Cardiac Surgery) in choosing between percutaneous coronary intervention and coronary artery bypass graft surgery in cases of complex coronary artery disease. There is paucity of data on the implementation of these recommendations in daily practice, and on the consequences of guideline discordant revascularization. Methods: This was a retrospective analysis of a prospective national survey of consecutive real world patients undergoing coronary revascularization for complex coronary artery disease according to decisions of local heart team at each center. SS was calculated at a dedicated CoreLab, and patients were classified as heart team/guidelines agreement/discordant. Results: Nine hundred seventy-nine patients (571 percutaneous coronary intervention and 408 coronary artery bypass graft) were included. Mean age was 65 years and the mean SS was 22. Heart team/guidelines discordance occurred in 170 (17.3%) patients. Independent predictors of heart team/guidelines discordance were age, admission to a center with no cardiac surgery service, SS, and previous percutaneous coronary intervention/myocardial infarction. A multivariate model based on these characteristics had a C statistic of 0.83. Thirty-day outcomes were similar in the agreement/discordance groups, however, heart team/guidelines discordance was associated with a significant increase in 3 year mortality (17.6% versus 8.4%; hazard ratio, 2.05; P =0.002) after multivariate adjustment. Conclusions: Heart team/guidelines discordance is not infrequent in real world patients with complex coronary artery disease undergoing revascularization. This is more likely to occur in elderly patients, those with more complex coronary disease (as determined by the SS), and those treated at centers with no cardiac surgery service. These patients have a higher risk for mid-term mortality.